Feeding Habits of Different Fish Species in Negombo Lagoon - Punchihewa, Neetha; Silva, M.P.C. (International Journal of Environment, 2019)
To investigate the feeding habits of different fish species in Negombo lagoon, fish species were collected from Kadolkele and Liyanagemulla sites during February 2015 to July 2015 using a drag net. Collected specimens were preserved in 5% formalin. Later, the fish specimens were dissected, and stomach contents were mixed with water to make a suspension. One ml of suspension was added to the Sedgewick Rafter cell, and examined under the light microscope. The occurrence %, volume %, numbers %, and the Relative Importance Values (RIV) were calculated. The gut contents of 62 samples from 12 fish species were analyzed; 11 species were found to feed on mangroves, 10 on seagrasses, and 8 on filamentous algae. 13 food items were identified. Most of the analysed fish were categorized as omnivores and opportunistic feeders. The juvenile fish mainly feed on a combination of mangroves, seagrasses and filamentous algae. Apart from plant matter, the juvenile fish were found to feed upon Cyclops sp. and mysids. Although Hemirhamphus marginatus is an omnivore, it specially fed on mangroves, seagrasses and filamentous algae. Furthermore, H. marginatus consumed common food items in both habitats except mangroves and molluscs, and the shifting of its diet was depended on the availability of food. The broadest niche breadth was recorded by H. marginatus and the shortest niche breadth by the herbivorous fish species, Siganus vermiculatus and Liza macrolepis. Caranx sexfasciatus exhibited an ontogenetic shift in their diet. The smaller C. sexfasciatus was a carnivore and the larger individuals of the same species were herbivores.